ANALLISIS MANFAAT PENYULUHAN DAN PELATIHAN PEMASARAN SECARA ONLINE (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
Jarak village, Wonosalam Subdistrict, Jombang Regency, east java is a village that has the potential of local potential such as mangosteen, coffee, salak, etawa goat’t milk and spices but from this potentials the community has problems in marketing. From this problem we conducted an extension program and online marketing training program. Through rapid technological developments make online marketing a way to attract consumers. By using online media, can make it easier for people to do marketing. Media that is often used by the general public to do online marketing such as facebook, instagram, and others. The advantages of online marketing; can save time, place and cost, without limits of time and place, easy to control and ease management of human resources.